ADAPTIVE ITERATIVE BEM-FEM COUPLING PROCEDURES TO ANALYZE INELASTIC MODELS - Soares Jr, D.; Godinho, L. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The analysis of complex systems may be more effectively handled considering the combination of different numerical methods, in a way that each numerical technique can be applied to deal with the particularities of the model that better fit its positive features. In this sense, the adaptive iterative coupling of the Boundary Element Method (BEM) and of the Finite Element Method (FEM) is discussed here, taking into account static nonlinear models. Optimal relaxation parameters are employed to speed up the convergence of the iterative coupling, and non-matching discretizations at common interfaces, as well as adaptive refinement within the FEM subdomains, are allowed, enabling more versatile and accurate approaches. A single unified iterative loop is considered in order to deal with all the focused iterative solutions simultaneously (i.e., the nonlinear analysis, the adaptive analysis and the coupling analysis), rendering a very efficient methodology. In this context, multiple sequential iterative loops, which represent a rather computationally demanding approach, can be avoided without significantly increase the number of the iterative steps of the dominant iterative process, considerably improving the performance of the method. At the end of the paper, numerical results are presented, illustrating the potentialities and the effectiveness of the proposed techniques.